Comparison of Surgical Outcomes Between Invasive Mucinous and Non-Mucinous Lung Adenocarcinoma - Matsui, Takuya; Sakakura, Noriaki; Koyama, Shin; Nakanishi, Keita; Sasaki, Eiichi; Kato, Seiichi; Hosoda, Waki; Murakami, Yoshiko; Kuroda, Hiroaki; Yatabe, Yasushi (The Annals of thoracic surgery, 2021)
Invasive mucinous adenocarcinoma (IMA) is a rare subtype of invasive lung adenocarcinoma. However, the clinical course and prognostic outcomes following IMA resection, particularly postoperative recurrence, remain unclear. We pathologically reevaluated 1362 lung adenocarcinoma resections performed at our institution, categorizing cases into the IMA group (72 cases) and non-IMA group (1290 cases). The IMA group was further classified into pneumonia and nodular types based on preoperative computed tomography. Overall, the IMA group had lower carcinoembryonic antigen levels (3 vs 8 ng/mL; P < .01), fewer lymph node metastasis (4% vs 24%; P < .01), and more KRAS mutations (56% vs 7%; P < .01) than the non-IMA group. Although postoperative recurrence rates did not differ between both groups (32% vs 27%; P = 0.35), lung recurrence occurred more frequently in the IMA group (83% vs 17%; P < .01). Propensity score-matched pair analysis showed that the IMA group had fewer lymph node metastasis (3% vs 35%; P < .01), more KRAS mutations (56% vs 9%; P < .01), and higher intrapulmonary recurrence rate (84% vs 31%; P < .01) than the non-IMA group. The 5-year overall survival rates did not differ between both groups (74% vs 81%; P = 0.26). However, among patients with intrapulmonary recurrence, those in the IMA group had significantly worse prognosis than those in the non-IMA group (35% vs 77%; P < .01). Intrapulmonary recurrence, which induced significantly worse prognosis, was more likely to occur in the IMA than non-IMA group. [Display omitted]